Burden of chronic diseases associated with periodontal diseases: a retrospective cohort study using UK primary care data. Issue 12 (19th December 2021) - Zemedikun, Dawit T; Chandan, Joht Singh; Raindi, Devan; Rajgor, Amarkumar Dhirajlal; Gokhale, Krishna Margadhmane; Thomas, Tom; Falahee, Marie; De Pablo, Paola; Lord, Janet M; Raza, Karim; Nirantharakumar, Krishnarajah
Abstract : Objectives: To identify the association between periodontal diseases (gingivitis and periodontitis) and chronic diseases including cardiovascular disease, cardiometabolic disease, autoimmune disease and mental ill health. Design: Retrospective cohort. Setting: IQVIA Medical Research Data-UK between 1 January 1995 and 1 January 2019. Participants: 64 379 adult patients with a general practitioner recorded diagnosis of periodontal disease (exposed patients) were matched to 251 161 unexposed patients by age, sex, deprivation and registration date. Main outcome measures: Logistic regression models accounting for covariates of clinical importance were undertaken to estimate the adjusted OR (aOR) of having chronic diseases at baseline in the exposed compared with the unexposed group. Incidence rates for each outcome of interest were then provided followed by the calculation of adjusted HRs using cox regression modelling to describe the risk of outcome development in each group. Results: The average age at cohort entry was 45 years and the median follow-up was 3.4 years. At study entry, the exposed cohort had an increased likelihood of having a diagnosis of cardiovascular disease (aOR 1.43; 95% CI 1.38 to 1.48), cardiometabolic disease (aOR 1.16; 95% CI 1.13 to 1.19), autoimmune disease (aOR 1.33; 95% CI 1.28 to 1.37) and mental ill health (aOR 1.79; 95% CI 1.75 to 1.83) compared with the unexposed group. During the follow-up of individuals without pre-existing outcomes of interest, the exposed group had an increased risk of developing cardiovascular disease (HR 1.18; 95% CI 1.13 to 1.23), cardiometabolic disease (HR 1.07; 95% CI 1.03 to 1.10), autoimmune disease (HR 1.33; 95% CI 1.26 to 1.40) and mental ill health (HR 1.37; 95% CI 1.33 to 1.42) compared with the unexposed group. Conclusions: In this cohort, periodontal diseases appeared to be associated with an increased risk of developing cardiovascular, cardiometabolic, autoimmune diseases and mental ill health. Periodontal diseases are very common; therefore, an increased risk of other chronic diseases represent a substantial public health burden.